A Forensic Framework for gathering and analyzing Database Systems using Blockchain Technology - Alzahrani, Ahmed Omar; Al-Khasawneh, Mahmoud Ahmad; Alarood, Ala Abdulsalam; Alsolami, Eesa (Engineering, Technology & Applied Science Research, 2024)
A blockchain is a distributed database that contains the records of transactions that are shared among all members of a community. Most members must confirm each and every transaction in order for a fraudulent transaction to fail to occur. As a rule, once a record is created and accepted by the blockchain, it cannot be altered or deleted by anyone. This study focuses on improving the investigation task in the database forensics field by utilizing blockchain technology. To this end, a novel conceptual framework is proposed for the forensic analysis of data from database systems engaging blockchain technology. This is the first time that blockchain technology is followed in database forensics for the purpose of tracing digital evidence. The design science research method was adopted to accomplish the objectives of the present study. The findings displayed that with the developed forensics framework, the data regarding database incidents could be gathered and analyzed in a more efficient manner.